Development and trade competitiveness of the European wine sector: A gravity analysis of intra-EU flows - Pasquale Lombardi; Andrea Dal Bianco; Roberto Freda; Francesco Caracciolo; Luigi Cembalo (Wine Economics and Policy)
This study analyses the intra-EU trade of the world׳s chief wine exporters, namely Italy, France and Spain. Using an augmented version of the gravity model we empirically assess which of the three countries have experienced growth in intra-EU market trade. Effects of transportation costs, as well as demand and supply gaps between origin and destination countries, on the size of bilateral trade flows were specifically taken into account. Estimation results highlight the differences between bulk and bottled wine, providing useful information for European producers and policy-makers involved on regulation of wine sector. As concern bulk wine, Italy and Spain show no element of growth in competitiveness, while France shows a statistically significant annual decrease. In contrast, estimates for bottled wine all show a growth tendency, albeit with a different magnitude of coefficients. Italy is the country with the highest trend, followed by Spain and France which instead has a decidedly modest growth in export values. However, analysis of pricing policies shows that France does not appear to target an increase in export volumes so much as an increase in average unit price, while Italy, and especially Spain, have a tendency to increase export volumes, also to the detriment of prices.